Chapter Bambini in tempo di guerra. Raccontare il passaggio della guerra e la Resistenza attraverso video-interviste di testimonianza: luoghi, memorie, racconti - Spiganti, Mario (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper aims at dealing mainly with infantry and it is carried on with methodological reflections, oral history research and audio-visive narrations. It sums up some issues about how to use oral and audio-visive sources on a didactic basis. Afterwards, the paper aims at dealing with the front passage in Tuscany in 1944 a Carda (Casentino region) and Florence. The paper describes and uses five interviews reacheable through the following link.